2014
DOI: 10.1002/app.41015
|View full text |Cite
|
Sign up to set email alerts
|

Surface relief gratings induced by pulsed laser irradiation in low glass‐transition temperature azopolysiloxanes

Abstract: Polymers capable of generating surface relief gratings (SRGs) were studied intensively in the last period for their applications in hot research areas, such as data storage, solar energy conversion, plasmonics, and biology. In the case of azopolymers, SRGs can be generated by two main procedures: pulsed or continuous laser irradiation. In this article, we discuss the possibility of obtaining stable SRGs with azopolysiloxanes with low glass‐transition temperature values, depending on the illumination type. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Because of the very short irradiation times (6 nanoseconds) used in the pulsed mode, the mechanism responsible for the periodic SRGs profile generation involves the fringe pattern produced by the interference of the diffracted beams. They act through two possible mechanisms, namely, a very fast supramolecular reorganization process, induced by the azo-groups dipole orientation [ 50 ], and material photo-fluidization, induced by the trans–cis isomerization process of the azo-segments in the exposed regions [ 20 , 24 , 51 ]. This competes with the larger proper volume required by the cis conformation [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the very short irradiation times (6 nanoseconds) used in the pulsed mode, the mechanism responsible for the periodic SRGs profile generation involves the fringe pattern produced by the interference of the diffracted beams. They act through two possible mechanisms, namely, a very fast supramolecular reorganization process, induced by the azo-groups dipole orientation [ 50 ], and material photo-fluidization, induced by the trans–cis isomerization process of the azo-segments in the exposed regions [ 20 , 24 , 51 ]. This competes with the larger proper volume required by the cis conformation [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mainly, this mass displacement can take place from UV laser-exposed areas to the unexposed areas. Recently, it was demonstrated that also an inverse mass displacement can occur, from the dark regions to the illuminated ones [ 24 ]. The arguments for the development of the azobenzene photoisomerization process by inversion or rotation are the subject of numerous molecular simulation studies [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each one of these two features is useful to orient the azo‐mesogenic groups into a specific direction, and thus induce properties of practical interest like birefringence, dichroism and chirality, among others. Moreover, the photo‐isomerization is helpful to induce a mass migration in thin or thick films, leading to the formation of micro‐scale surface relief gratings (SRG) of regular profile . Both, the light‐induced orientation and mass migration make the liquid crystal azopolymers potential candidates for many applications, particularly for volume or high density (terabytes) data storage memories.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In this case, direct and effi cient optical inscription of relief patterns can be achieved on thin azo-fi lms by a spatially modulated illumination. [9][10][11][12][13] In this case, direct and effi cient optical inscription of relief patterns can be achieved on thin azo-fi lms by a spatially modulated illumination.…”
mentioning
confidence: 99%